A View of a Traditional Foundry’s Leadership - Do they follow the Chinese Cultural in the way they lead? - Zhang,Xiao Yan; Sandin,Jenny (2008)
Goals of this thesis is to investigate how the Foundry Chinese Managers perceive leadership, and how they construct their leadership skills in their daily working environment in that specific foundry context and whether the Chinese leadership is still following the traditional Chinese Culture or they have their own ways to lead. We are using a qualitative/inductive method. We are using already existing theories and testing these by conducting interviews. The data that we are collecting are deep and detailed.
Keywords: Chinese Culture; Leadership; Eustress Emotional Attachment; Conflict Resolution; Motivation; Management of enterprises; Företagsledning, management